Biochemical profiling of the coagulation–fibrinolysis system and a three-tier stratified testing workflow in non-small cell lung cancer - Miao, Yongshuai; Yan, Yue; Zhao, Rui; Zhao, Ying; Li, Xiaohua (Journal of Medical Biochemistry, 2026)
Background: In routine clinical practice, the general workflow for coagulation–fibrinolysis testing has not been specifically designed for non-small cell lung cancer (NSCLC), and its ability to identify and warn of thrombotic risk in this population remains limited. This study aimed to systematically characterize the full-pathway biochemical profile of the coagulation–fibrinolysis system in patients with NSCLC and to establish and validate an optimized standardized testing workflow tailored to this population. Methods: A total of 148 subjects who met the inclusion and exclusion criteria between January 2024 and June 2025 were enrolled, including 64 healthy controls, 45 patients with benign lung disease, and 39 patients with pathologically confirmed NSCLC. After fasting venous blood samples had been collected and pretreated, routine coagulation–fibrinolysis indices, coagulation factor activities, fibrinolytic regulatory markers, and vascular endothelial injury markers were quantitatively measured using a Sysmex CS-5100 fully automated coagulation analyzer, a Sysmex XN-1000 fully automated hematology analyzer, and a Roche Cobas e 602 fully automated chemiluminescence immunoassay analyzer. Standardized quality control was implemented throughout the analytical process, and the performance of the testing systems was verified. At the same time, an NSCLC-specific three-tier stratified precision testing workflow was established and compared in a paired manner with the conventional non-differentiated routine clinical testing workflow. Results: Compared with both the Control group and the benign lung disease group, the NSCLC group showed significant differences in routine core coagulation–fibrinolysis indices, coagulation factor activities, fibrinolytic regulatory markers, and endothelial injury markers (P<0.05). For the same specimens, the results obtained before and after workflow optimization remained highly consistent, and the intraclass correlation coefficients (ICCs) for all indices were ≥0.90. After optimization, the median within-run coefficient of variation (CV) decreased from 2.9% to 1.7%, and the median between-run CV decreased from 5.4% to 3.4%. The relative deviation from international reference materials was also reduced (P<0.001). In clinical application, the median specimen turnaround time fell from 101.0 min to 69.0 min, while the median average testing cost per patient decreased from 332.0 yuan to 238.0 yuan (P<0.05). Conclusion: The NSCLC-specific three-tier stratified coagulation–fibrinolysis testing workflow established in this study improved analytical performance and workflow efficiency while remaining clinically practical, providing a standardized laboratory approach for coagulation assessment and early thrombotic risk management in patients with NSCLC.